INFORMED CONSENT STATUS IN OBSERVATIONAL STUDIES WITH RETROSPECTIVE DESIGN: A POOR SHOW - Gill, Supreet Kaur; Gupta, Vikas; Bansal, Parveen (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Informed consent is very important to protect the rights of patients and is obtained as a vital component of any clinical study. Requirement of patient consent in retrospective research continues to stir controversy even today. Some of directions of regulatory authorities even waive off the consent for retrospective studies, whereas few recommend that at least clearance from the Ethical Review Board may be taken or information to patient may be given or oral consent must be given by patient for usage of the data in any retrospective study. The aim of this study was to analyze the current status of informed consent procedures in observational studies with retrospective design. Methods: This review was intended to find out the current status of procedures involved in informed consent in India and abroad. A total of 100 retrospective studies were searched for this objective from the internet and other literature sources. Results: Data show that in 65% of studies neither informed consent/oral consent nor ethical clearance was taken. Only 1% of studies have been conducted with informed consent as well as ethical clearance. Only 14% of studies were conducted with informed consent and 21% with ethical approval. Conclusion: The study reflects very poor status of informed consent in retrospective studies and noncompliance of ICH guidelines for clinical research in relation to informed consent. Keywords: Clinical research, Informed consent, Retrospective studies.